Fortunately, the milk - Gaiman, Neil; Young, Skottie (New York : Harper, 2013)
While picking up milk for his children's cereal, a father is abducted by aliens and finds himself on a wild adventure through time and space.
Ages 8-12.
Keywords: Space and time -- Juvenile fiction; Action and adventure fiction